Tennis Ball Marker and related PGE mineralization in the Eastern Bushveld Complex, South Africa - Khoza, Busisiwe (My University, 2021)
At the Rustenburg Layered Suite, orthopyroxenite is interlayered with gabbros, gabbronorite, norites, anorthosites, etc. However, the Main Zone margins show a puzzling feature with spherical orthopyroxenite encased in gabbronorite, norite, and anorthosite. This feature is called the Tennis Ball Marker. Lee and Sharper (1979) interpreted it as a result of the spherical aggregation of orthopyroxene crystals suspended in a magma. The study aims to propose a new model to explain the origin of the spherical orthopyroxenite located at the Tennis Ball Marker, based on field observations, bulk chemical data, mineral compositions, and Rb-Sr, Sm-Nd, and Lu-Hf isotope data. Our results show that: (1) the spherical orthopyroxenite and the gabbronorite matrix are composed of the same mineral assemblage made up of plagioclase, orthopyroxene, clinopyroxene, quartz, biotite, oxides, and sulphides; (2) the spherical orthopyroxenite and the gabbronorite matrix are petrographically distinct; (3) the orthopyroxene and plagioclase on the spherical orthopyroxenite have a higher Magnesium number (Mg#) and Anorthite content (An), respectively, compared to those on the gabbronorite matrix; (4) the whole rock Mg# and normative anorthite content on the spherical orthopyroxenite cumulates, is higher than those of the gabbronorite matrix; (5) the feldspar and pyroxene geothermometers show that the cumulates on the spherical orthopyroxenite crystallized at a higher temperature than those on the gabbronorite, (6) The whole-rock trace elements distribution diagram for the spherical orthopyroxenite and the gabbronorite matrix have contrasting Ba and Sr anomalies; (7) The spherical orthopyroxenite show a negative and no Eu anomaly, which contrast the positive Eu anomaly shown by the gabbronorite matrix and host; (8) the REE patterns of the gabbronorite matrix are steeper than those of the spherical orthopyroxenite; (9) the spherical orthopyroxenite cumulates and the gabbronorite matrix have similar Sri (0.706490 − 0.7077254); Ndi (0.509622 − 0.0509703); Hf i (0.281139−0.281241); ꜫNd (-6.7 to -5.1) and ꜫHf (-11.7 to -8) values are also homogenous with height. iv The isotopic data shows that the spherical orthopyroxenite and the gabbronorite crystallized from a magma with the same isotopic signature. The bulk composition, REE patterns, and the mineral composition data imply that the gabbronorite crystalized from the residual melt of the spherical orthopyroxenite. The hypothesis envisages an intrusion of an orthopyroxene saturated magma that underwent fractional crystallization to form an orthopyroxenite layer at the base. The fractionation of orthopyroxene crystals caused the residual magma to evolve (at the chamber and feeder) to the eutectic. The magma with the eutectic composition ascended on the feeder to the chamber, and it broke the orthopyroxenite layer at the base as it was opening the magma chamber. The new magma percolated in between the orthopyroxenite fragments, eroded, and transported them to the south. The spherical shapes of the orthopyroxenite were achieved by a chemical dissolution process that eroded the edges and corners faster than the planar surface
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Geology to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2021